Hospitalizations Associated With Strongyloidiasis in the United States, 2003–2018 . (21st March 2022) - Inagaki, Kengo; Bradbury, Richard S; Hobbs, Charlotte V
Abstract: Background: Strongyloides stercoralis is considered to be historically endemic in Appalachia and the American South, but recent surveillance data, especially data evaluating strongyloidiasis associated with hospitalization, are lacking in most parts of the United States. Methods: We performed a population-based retrospective analysis on strongyloidiasis using the National Inpatient Sample from 2003 to 2018. Geographic distribution of strongyloidiasis associated hospitalization was assessed. Logistic regression was used to identify risk factors associated with strongyloidiasis. Results: We identified 6931 hospitalizations associated with strongyloidiasis during the study period (11.8 per million hospitalizations). The rate of strongyloidiasis was highest in the Northeast US region, including the Middle Atlantic division (47.1 cases per million population; adjusted odds ratio, 2.00 [95% confidence interval: 1.58–2.53]), and the East South Central division (27.5 cases per million; adjusted odds ratio, 2.77 [2.02–3.80]). Older age, male sex, nonwhite race/ethnicity (particularly Hispanic and Asian), nonprivate insurance, and residence in neighborhoods with low median income were also associated with strongyloidiasis. Immunocompromising conditions, particularly human immunodeficiency virus infection, were present in 41.3% of hospitalizations with strongyloidiasis. In-hospital death occurred in 7.8% of patients with strongyloidiasis-associated hospitalization. Conclusions: Strongyloidiasis-associated hospitalization is rare in the United States but can be associated with increased mortality rate/mortality risk . It occurs more frequently in poor and marginalized populations. Immunocompromised conditions were common among hospitalized patients with strongyloidiasis. Enhanced surveillance efforts are needed to inform health policies for improving the health of at-risk populations. Abstract : Strongyloidiasis-associated hospitalization is rare in the United States but occurs preferentially in marginalized people and can be associated with mortality. It is relatively common in the Northeast region in addition to the South region. Enhanced surveillance effort is needed.